2020
DOI: 10.1177/1533033820951807
|View full text |Cite
|
Sign up to set email alerts
|

Change of Serum Inflammatory Cytokines Levels in Patients With Chronic Obstructive Pulmonary Disease, Pneumonia and Lung Cancer

Abstract: Objective: This study aimed to investigate the serum inflammatory cytokines levels in patients with COPD, pneumonia and lung cancer, and assess the correlation between the levels of inflammatory cytokines levels and development of these diseases. Methods: Two hundred thirty-two patients including 114 patients with pneumonia, 76 patients with chronic obstructive pulmonary disease (COPD) and 42 patients with lung cancer, and 62 age-matched healthy volunteers as controls were enrolled. The pro-inflammatory cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…T lymphocytes released EVs that reduced cell viability and induced significant production of inflammatory cytokines IL-6, MCP-1, MCP-9 and TNF-a in human bronchial epithelial cells (HBEs), with decreased levels of anti-inflammatory cytokine IL-10 [ 29 ]. IL-6 and TNF-a both have a role in the acute phase response of COPD, and TNF-a particularly is significantly associated with disease progression [ 68 ]. Together the studies showed that upon CS exposure, epithelial cells, T lymphocytes and neutrophils release increased levels of EVs containing biomolecules that further enhance the inflammatory response and degrade the ECM, causing lung tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…T lymphocytes released EVs that reduced cell viability and induced significant production of inflammatory cytokines IL-6, MCP-1, MCP-9 and TNF-a in human bronchial epithelial cells (HBEs), with decreased levels of anti-inflammatory cytokine IL-10 [ 29 ]. IL-6 and TNF-a both have a role in the acute phase response of COPD, and TNF-a particularly is significantly associated with disease progression [ 68 ]. Together the studies showed that upon CS exposure, epithelial cells, T lymphocytes and neutrophils release increased levels of EVs containing biomolecules that further enhance the inflammatory response and degrade the ECM, causing lung tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…31 Previous clinical studies have shown the importance of the pro-inflammatory factor IL-6 and the anti-inflammatory factor IL-10 in COPD. [32][33][34][35] IL-6 can promote overexpression of VEGF, leading to the formation of proliferative lesions of the vasculature. 36 The results of this study showed that after 2-8 weeks of treatment, IL-6 expression was significantly increased, while IL-10 expression was significantly decreased in the lung tissues of rats in the model groups.…”
Section: Discussionmentioning
confidence: 99%
“…Available data on the systemic levels of IL-10 in COPD are rather contradictory. A number of studies have demonstrated high serum IL-10 levels in patients with COPD [ 55 , 56 ]. At the same time, there are publications indicating a low concentration of IL-10 in the blood in severe COPD [ 54 ].…”
Section: Discussionmentioning
confidence: 99%